A Multilevel Perspective to Social Media Influentials' Frame Building Across Crises. (August 2023) - Zhao, Xinyan
Social media influentials play key roles in information creation and impact people's crisis interpretations and behavioral intentions. Applying a multilevel perspective, this study examined how various social media influentials' frame building was affected by crisis clusters and message characteristics. Social media influentials' tweets were extracted from over a million tweets from eight crises. A random sample of 2, 000 tweets was analyzed by content analysis. The results showed that social media influentials' use of responsibility and topic frames was affected by both crisis-level factors (i.e., crisis origin and organization type) and message-level factors (i.e., communicative functions and types of influentials). These findings support the importance to understand the contextual factors that condition influentials' frame building on social media.